LEGAL REGULATION OF ENSURING HUMAN LIFE SAFETY ON WATER BODIES IN THE CONSTITUENT ENTITIES OF THE RUSSIAN FEDERATION: A COMPARATIVE LEGAL ANALYSIS - ABANINA Elena Nikolaevna (Правовое государство: теория и практика)
The recreational use of water bodies, namely for tourism, physical culture and sports, recreation and health promotion of citizens, including recreation for children and their health improvement, is carried out in accordance with the norms of federal and regional legislation, which is often characterised by gaps, contradictions and other defects, which affects the effectiveness of legal regulation of this area of social relations. Statistical data indicating an increase in the number of accidents on water bodies related to non-compliance with water legislation and leading to death and injury of people, confirm the need to study this t ype of use of water bodies. Purpose: to analyse normative legal acts of the constituent entities of the Russian Federation (on the example of the Volga Federal District) in the sphere of the recreational use of water bodies, ensuring human safety on water bodies and to develop proposals to eliminate the identified contradictions. Methods: systemic and structural-functional analysis, as well as special legal methods: comparative legal, formal legal, interpretation. Results: the article gives scientifically based recommendations for improving the federal and regional legislation regulating the recreational use of water bodies and ensuring human safety.